QUANTO É:x-y=6
x+y=-7
Soluções para a tarefa
Respondido por
4
x=6+y
Vamos substituir na segunda equação:
x+y= -7
6+y+y=-7
2y=-7-6
2y=-13
y=-13/2
e x é:
x= 6+y
x=6+ (-13/2)
x= 12-13/2
x= -1/2
Respondido por
4
vamos lá...
x - y=6
x+ y= -7
sistema pelo método da adição
somar:
substituir x em:
![x+y=-7 \\ \\ - \frac{1}{2} +y=-7 \\ \\ mmc=2 \\ \\ -1+2y=-14 \\ \\ 2y=-14+1 \\ \\ 2y=-13 \\ \\ y=- \frac{13}{2} \\ \\ S=\{(- \frac{1}{2} ,- \frac{13}{2} )\} x+y=-7 \\ \\ - \frac{1}{2} +y=-7 \\ \\ mmc=2 \\ \\ -1+2y=-14 \\ \\ 2y=-14+1 \\ \\ 2y=-13 \\ \\ y=- \frac{13}{2} \\ \\ S=\{(- \frac{1}{2} ,- \frac{13}{2} )\}](https://tex.z-dn.net/?f=x%2By%3D-7+%5C%5C++%5C%5C+-+%5Cfrac%7B1%7D%7B2%7D+%2By%3D-7+%5C%5C++%5C%5C+mmc%3D2+%5C%5C++%5C%5C+-1%2B2y%3D-14+%5C%5C++%5C%5C+2y%3D-14%2B1+%5C%5C++%5C%5C+2y%3D-13+%5C%5C++%5C%5C+y%3D-+%5Cfrac%7B13%7D%7B2%7D++%5C%5C++%5C%5C+S%3D%5C%7B%28-+%5Cfrac%7B1%7D%7B2%7D+%2C-+%5Cfrac%7B13%7D%7B2%7D+%29%5C%7D)
x - y=6
x+ y= -7
sistema pelo método da adição
somar:
substituir x em:
Perguntas interessantes